Efficient carbonized recycled aggregate concrete and preparation method thereof

By using moisturizing SAP particles in recycled aggregate concrete to form CO2 transmission channels, the high cost and unevenness problems in the carbonization process of recycled aggregates are solved, and efficient and uniform carbonization effect and concrete performance improvement are achieved.

CN119191778APending Publication Date: 2024-12-27INST OF ECONOMIC & TECH STATE GRID HEBEI ELECTRIC POWER +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411143110.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-20
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In the prior art, there are problems such as high cost, high energy consumption and limited application scenarios in the carbonization process of regenerated aggregates, and uneven carbonization and slow carbonization rate affect the performance improvement of regenerated aggregates.

Method used

Moisturizing SAP particles are used to form CO2 transmission channels in regenerated aggregate concrete. Through its excellent water absorption and water retention ability, CO2 capture and carbonization reaction are promoted, and the carbonization efficiency of regenerated aggregates and the mechanical properties of concrete are improved.

Benefits of technology

It realizes that the CO2 capture efficiency and carbonization rate of recycled aggregates can be improved while ensuring the strength of concrete, reduces the carbonization cost, and has a uniform carbonization effect, which is suitable for large-scale applications.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of cement-based building materials, in particular to efficient carbonization type recycled aggregate concrete and a preparation method of the efficient carbonization type recycled aggregate concrete. Moisturizing type SAP particles are prepared through research and development and added into recycled aggregate concrete, the mixing amount of the moisturizing type SAP particles is controlled, a good CO2 transmission channel is formed, it is guaranteed that the strength of the recycled aggregate concrete is not reduced due to addition of the moisturizing type SAP particles, the moisturizing type SAP particles have the excellent water absorption capacity and water retention effect, CO2 capture is promoted, and the moisture retention effect of the recycled aggregate concrete is improved. The reinforcement of the recycled aggregate and the enhancement of the mechanical property of the concrete are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cement-based building materials, and in particular to a high-efficiency carbonized recycled aggregate concrete and a preparation method thereof. Background Art

[0002] Recycled aggregate refers to the aggregate obtained by removing the steel bars from the waste concrete and then crushing and screening it to obtain aggregate with similar properties to natural aggregate. However, due to the presence of a layer of hardened cement paste with a complex interface on the surface of the recycled aggregate, the mechanical properties and durability of the recycled aggregate are often lower than those of natural aggregate. However, through carbonization reaction, the calcium hydroxide (Ca(OH) 2 ), calcium silicate hydrate gel (CSH) is converted into calcium carbonate (CaCO 3 ), thereby reducing porosity, improving pore structure, and enhancing the compactness and strength of recycled aggregate concrete. Therefore, promoting the carbonization of recycled aggregate is the key to achieving large-scale recycling of recycled aggregate.

[0003] Traditionally, due to the presence of CO in the atmosphere 2 The carbonization rate of recycled aggregate in the atmosphere is slow due to its low content. In order to speed up the carbonization rate, CO 2 However, the current CO 2 The high cost of carbonization maintenance and the limited application scenarios of instruments and equipment limit the application of CO 2 Application of carbonization curing in engineering.

[0004] Reference 1 (Pu Shengpeng, Sun Yi, Mou Xingming, et al. Study on the performance of pressurized carbonized recycled concrete coarse aggregate [J]. Chongqing Architecture, 2023, 22(02): 57-59.) published a method for carbonizing recycled aggregate. The method is to place the recycled aggregate in a carbonization furnace, evacuate it, and introduce 99.5% concentration of CO 2 , Ca(OH) in the hardened cement paste attached to the surface of the recycled aggregate 2 and CSH to CaCO 3 , thereby improving the performance of recycled aggregates. High concentrations of CO 2 It can accelerate the carbonization of recycled aggregates.

[0005] Reference 2 (Songhui L, Peiliang S, Dongxing X, et al. A comparison of liquid-solid and gas-solid accelerated carbonation for enhancement of recycled concrete aggregate [J]. Cement and Concrete Composites, 2021, 118, 103988.) discloses a method for wet carbonization of recycled aggregate. The method is to place the recycled aggregate in a metal mesh, then soak it in tap water, and inject 99.9% industrial-grade CO into the water through a flow controller and a bubble controller. 2 Compared with dry carbonization, wet carbonization is more efficient, and the hardened cement paste remaining on the surface of recycled aggregate can generate more carbonization products.

[0006] The shortcomings of the above technology are:

[0007] (1) In Reference 1, high concentration CO is injected into the carbonization furnace. 2 Carbonize the recycled aggregate. Although this method helps to improve the carbonization efficiency of recycled aggregate, the high concentration of CO used in the carbonization process 2 The cost is high, and the capacity of the carbonization furnace used is limited, the energy consumption is high, the application scenarios are limited, and the large-scale carbonization of recycled aggregates cannot be achieved. In the early stage of curing, the carbonization rate of recycled aggregates is fast. As the curing time increases, the generated CaCO 3 Gradually block the pores and inhibit CO 2 The penetration of recycled aggregate is not conducive to the further carbonization of recycled aggregate. In addition, the placement of recycled aggregate in the carbonization furnace can also lead to uneven carbonization, affecting the carbonization effect of recycled aggregate.

[0008] (2) Although the wet carbonization method used in Reference 2 can accelerate the carbonization rate of recycled aggregates, it still has some shortcomings. First, the wet carbonization method requires a lot of energy to convert CO 2 It is bubbling into water and requires special equipment to control and maintain the carbonization process, which increases the carbonization cost of recycled aggregates. In addition, the carbonization effect of recycled aggregates increases with the increase of carbonization curing time, but in actual engineering, it is impossible to increase the carbonization curing time indefinitely. This method also involves pressurization treatment, but the realization of pressurization is highly dependent on safe and sealed pressurization equipment, which limits the application scope of wet carbonized recycled aggregates.

[0009] The inventors have conducted a systematic study on the effects of SAP particles in concrete in the early stage, and have also achieved research results on accelerating the carbonization of concrete, and applied for patent CN113416090A. The study shows that the micropores generated by SAP particles in the mortar can form CO 2 transmission channel, and can absorb water in a humid environment to improve the air permeability of the mortar, and release water to keep the mortar moist after the mortar dries, thereby improving the CO 2 The capture efficiency of recycled aggregate concrete is 2-5% of the mass of the cementitious material, and a high water-binder ratio and fine sand are used. However, high SAP particle dosage and high water-binder ratio will inevitably reduce the mechanical properties of cement-based materials. How to improve the CO2 capture efficiency of recycled aggregate concrete while ensuring the mechanical properties? 2 Capture efficiency is a technical problem that has yet to be solved. Summary of the invention

[0010] In order to overcome the problems existing in the prior art, the present invention provides a highly efficient carbonized recycled aggregate concrete. Specifically, the present invention adopts commonly used cement and admixtures as cementitious materials, adopts fully recycled aggregate, and prepares a moisture-retaining SAP particle through research and development and adds it to the recycled aggregate concrete, so that its mass accounts for 1-2% of the mass of the cementitious material, so as to form a good CO 2 The addition of moisturizing SAP particles does not reduce the strength of recycled aggregate concrete. The moisturizing SAP particles have excellent water absorption capacity and water retention effect, which promotes CO 2 Capture to achieve the strengthening of recycled aggregates and the enhancement of concrete mechanical properties.

[0011] Specifically, the high-efficiency carbonized recycled aggregate concrete of the present invention is composed of the following raw materials in parts by weight:

[0012] 280-310 parts of cement, 200-230 parts of admixture, 800-860 parts of recycled fine aggregate, 1000-1040 parts of recycled coarse aggregate, 10-12 parts of water reducer, 6-8 parts of moisturizing SAP particles, 190-210 parts of water,

[0013] Wherein, the preparation process of the moisturizing SAP particles is:

[0014] a. Mix persulfate and water in a mass ratio of (1.1-1.2):6 and stir evenly to obtain material A.

[0015] b. Mix sodium bisulfite and water in a mass ratio of (0.9-1):5 and stir evenly to obtain material B.

[0016] c. Add acrylic acid, N-(4-ethynylphenyl) acrylamide, methoxy polyethylene glycol acrylate, polyethylene glycol diacrylate, N,N-dimethylformamide, and water in a mass ratio of (40-50):(10-12):(20-25):(15-18):(4-6):(280-300) into a reaction kettle and stir evenly to obtain a base material.

[0017] d. Heat the base material, add material A and material B dropwise, keep warm and stir to obtain a gel solution. The mass ratio of base material, material A and material B is 100:(1-1.1):(0.8-0.9).

[0018] e. Adjust the pH value of the gel solution to 7.2-7.4, filter, wash, dry, and ball-mill to 50-100 nm to obtain water-absorbing resin particles.

[0019] f. Mix the water-absorbing resin particles, polyethylene glycol and water in a mass ratio of 10:(1-1.2):100 and dry to obtain.

[0020] Existing technology shows that the carbonization rate of recycled aggregates will be accelerated in a humid environment. Moisture helps to improve the reaction conditions required for carbonization and promotes Ca 2+ and CO 3 2- The diffusion between the two, thus accelerating the carbonization process, SAP particles have a high water absorption effect, which can release moisture during the curing stage of cement-based materials and reduce drying shrinkage. They are often used as internal curing materials. The amount of SAP particles added is generally less than 1% of the mass of the cementitious material, otherwise it is easy to cause the loss of construction performance and mechanical properties of the cement-based material. The inventor's previous research used a high amount of SAP particles of 2-5% of the mass of the cementitious material and used a water-binder ratio of 0.5-0.8 to form abundant pores in the mortar, thereby forming CO 2 The transmission channel improves the carbonization effect of cement-based materials, but sacrifices the mechanical properties of mortar. Therefore, through a large number of experiments, the present invention uses acrylic acid, N-(4-ethynylphenyl) acrylamide, methoxy polyethylene glycol acrylate, polyethylene glycol diacrylate as polymerization monomers, selects N, N-dimethylformamide as a cross-linking agent, and polymerizes to prepare a moisturizing SAP with excellent water absorption and water retention effects, and crushes it to nanometer level, and then absorbs the loaded polyethylene glycol to obtain moisturizing SAP particles. It is found through experiments that adding 1-2% of it to cement-based materials can have good CO 2 Transmission capacity without loss of mechanical properties due to the formation of a large number of through holes.

[0021] There are a lot of micro cracks in recycled aggregates, which will reduce the mechanical properties of concrete. Studies have shown that carbonization can strengthen recycled aggregates. However, the carbonization rate of recycled aggregates under natural conditions is slow. The existing technology generally carbonizes them in an autoclave, which is costly, and the carbonization effect of recycled aggregates will be accelerated in a humid environment. The moisturizing SAP particles of the present invention have better water retention than ordinary SAP particles, and release water more slowly in cement-based materials, thereby maintaining humidity stability. The transmission channels formed by them can not only carbonize and strengthen cement-based materials, but also provide CO for the carbonization of recycled aggregates. 2 transmission channels and a continuously moist environment, thereby reinforcing the recycled aggregate and providing good compressive resistance for cement-based materials.

[0022] Preferably, the cement is at least one of Portland cement, ordinary Portland cement, sulphoaluminate cement and aluminate cement.

[0023] Preferably, the admixture is at least one of fly ash, mineral powder, silica fume, metakaolin, and activated coal gangue powder.

[0024] Preferably, the particle size of the recycled fine aggregate is 0.1-4.25 mm, and the fineness modulus is 2.2-2.4.

[0025] Preferably, the recycled coarse aggregate has a particle size of 5-16 mm and is continuously assembled.

[0026] Preferably, the water reducing agent is a polycarboxylic acid water reducing agent, and the water reducing rate is ≥20%.

[0027] Preferably, the persulfate in step a is ammonium persulfate.

[0028] Preferably, the stirring and insulating step d is carried out at 70-75° C. for 6-8 hours.

[0029] Preferably, anhydrous ethanol is used for washing in step e.

[0030] The present invention also relates to a method for preparing the above-mentioned high-efficiency carbonized recycled aggregate concrete, which specifically comprises the following steps:

[0031] 1) Weigh each raw material by weight,

[0032] 2) Add cement, admixture, recycled fine aggregate and moisturizing SAP particles into a mixer and mix them evenly to obtain a dry mix.

[0033] 3) Dissolve the water reducer in water to obtain an admixture solution.

[0034] 4) Add recycled coarse aggregate to the dry mix, stir, add admixture solution, stir evenly to obtain concrete slurry.

[0035] 5) The concrete slurry is molded, demoulded and cured.

[0036] Preferably, step 5) is performed by standard curing.

[0037] The present invention has the following technical advantages:

[0038] 1. The present invention uses fully recycled aggregate as concrete aggregate, eliminates industrial solid waste, and achieves cost reduction and waste utilization.

[0039] 2. The moisturizing SAP particles prepared by the present invention have good water absorption and water retention capabilities and can form CO at a dosage higher than 1% and lower than 2% of the prior art. 2 Transmission channel, and no high water-binder ratio is required, so carbon fixation can be achieved without reducing mechanical properties.

[0040] 3. The moisture-retaining SAP particles of the present invention can maintain the humidity of concrete stable and achieve continuous carbon fixation in cement-based materials.

[0041] 4. The recycled aggregate of the present invention can be directly used in concrete preparation without prior strengthening, and can be continuously carbonized and strengthened during the service of concrete.

[0042] 5. The concrete of the present invention has a simple preparation process, sustainable carbon fixation, excellent mechanical properties and broad application prospects. DETAILED DESCRIPTION

[0043] In order to characterize the technical effect of the present invention, recycled aggregate concrete was prepared and its performance was tested. In order to reflect the carbon fixation strengthening effect, a group of concrete specimens were cured to different ages and then dried for compressive strength test. Another group of specimens were demoulded, dried and weighed to obtain M, and then immersed in water for saturation treatment. The specimens were stored in CO 2 MCS was obtained by weighing after carbonization curing at different ages in a carbonization box with a concentration of 20%. n , dry and weigh to get MCG n , and then perform compressive strength test, and calculate carbonization weight gain C according to the weighing results n and moisturizing weight gain S n ,in:

[0044] The carbonization weight gain calculation formula is C n =(MCG n -M) / M*100%,

[0045] The formula for calculating moisturizing weight gain is S n =(MCS n -MCG n ) / M*100%,

[0046] n is the age, for example, carbonization curing to 7 days from the molding time is counted as C7 , S 7 , carbonization curing until 28 days from molding time is counted as C 28 , S 28 ,

[0047] During the test, P·O42.5 cement was used as cement, the particle size of recycled fine aggregate was 0.1-4.25mm, the fineness modulus was 2.3, the particle size of recycled coarse aggregate was 5-16mm continuously mixed, the water reducer was polycarboxylate water reducer, and the water reduction rate was 24.5%.

[0048] Example 1

[0049] High-efficiency carbonized recycled aggregate concrete is composed of the following raw materials in parts by weight:

[0050] 300 parts of cement, 130 parts of fly ash, 100 parts of mineral powder, 850 parts of recycled fine aggregate, 1010 parts of recycled coarse aggregate, 12 parts of water reducer, 7 parts of moisturizing SAP particles, 200 parts of water,

[0051] Wherein, the preparation process of the moisturizing SAP particles is:

[0052] a. Mix ammonium persulfate and water in a mass ratio of 1.1:6 and stir evenly to obtain material A.

[0053] b. Mix sodium bisulfite and water in a mass ratio of 1:5 and stir evenly to obtain material B.

[0054] c. Add acrylic acid, N-(4-ethynylphenyl) acrylamide, methoxy polyethylene glycol acrylate, polyethylene glycol diacrylate, N,N-dimethylformamide, and water into the reaction kettle at a mass ratio of 45:10:22:18:5:300, stir evenly, and obtain the base material.

[0055] d. Heat the base material, add material A and material B dropwise, keep warm and stir at 70°C for 7h to obtain a gel solution. The mass ratio of base material, material A and material B is 100:1.1:0.9.

[0056] e. The gel solution was adjusted to pH 7.3, filtered, washed, dried, and ball-milled to 50-100 nm to obtain water-absorbing resin particles.

[0057] f. Mix the water-absorbing resin particles, polyethylene glycol and water in a mass ratio of 10:1:100 and dry them to obtain the product.

[0058] After testing, the 7d compressive strength of concrete is 35.3MPa, the 7d carbonization compressive strength is 39.7MPa, the carbonization weight gain is 4.2%, the moisture retention weight gain is 4.9%, the 28d compressive strength is 52.6MPa, the 28d carbonization compressive strength is 59.5MPa, the carbonization weight gain is 6.6%, and the moisture retention weight gain is 3.4%.

[0059] Example 2

[0060] High-efficiency carbonized recycled aggregate concrete is composed of the following raw materials in parts by weight:

[0061] 290 parts of cement, 120 parts of fly ash, 60 parts of mineral powder, 30 parts of silica fume, 830 parts of recycled fine aggregate, 1040 parts of recycled coarse aggregate, 11 parts of water reducer, 8 parts of moisturizing SAP particles, 200 parts of water,

[0062] Wherein, the preparation process of the moisturizing SAP particles is:

[0063] a. Mix ammonium persulfate and water in a mass ratio of 1.1:6 and stir evenly to obtain material A.

[0064] b. Mix sodium bisulfite and water in a mass ratio of 0.9:5 and stir evenly to obtain material B.

[0065] c. Add acrylic acid, N-(4-ethynylphenyl) acrylamide, methoxy polyethylene glycol acrylate, polyethylene glycol diacrylate, N,N-dimethylformamide, and water into the reaction kettle in a mass ratio of 50:11:20:17:4:300, stir evenly, and obtain the base material.

[0066] d. Heat the base material, add material A and material B dropwise, keep warm and stir at 75°C for 6 hours to obtain a gel solution. The mass ratio of base material, material A and material B is 100:1:0.8.

[0067] e. The gel solution was adjusted to pH 7.3, filtered, washed, dried, and ball-milled to 50-100 nm to obtain water-absorbing resin particles.

[0068] f. Mix the water-absorbing resin particles, polyethylene glycol and water in a mass ratio of 10:1.2:100 and dry them to obtain the product.

[0069] After testing, the 7d compressive strength of concrete is 36.1MPa, the 7d carbonization compressive strength is 42.0MPa, the carbonization weight gain is 4.5%, the moisture retention weight gain is 5.2%, the 28d compressive strength is 53.7MPa, the 28d carbonization compressive strength is 61.5MPa, the carbonization weight gain is 6.9%, and the moisture retention weight gain is 3.5%.

[0070] Comparative Example 1

[0071] Recycled aggregate concrete is composed of the following raw materials in parts by weight:

[0072] 300 parts of cement, 130 parts of fly ash, 100 parts of mineral powder, 850 parts of recycled fine aggregate, 1010 parts of recycled coarse aggregate, 12 parts of water reducer, 15.9 parts of SAP particles used in invention CN113416090A, and 265 parts of water.

[0073] After testing, the 7d compressive strength of concrete is 19.5MPa, the 7d carbonization compressive strength is 23.6MPa, the carbonization weight gain is 3.9%, the moisture retention weight gain is 1.2%, the 28d compressive strength is 27.9MPa, the 28d carbonization compressive strength is 32.0MPa, the carbonization weight gain is 4.1%, and the moisture retention weight gain is 0.2%.

[0074] Comparative Example 2

[0075] Recycled aggregate concrete is composed of the following raw materials in parts by weight:

[0076] 300 parts of cement, 130 parts of fly ash, 100 parts of mineral powder, 850 parts of recycled fine aggregate, 1010 parts of recycled coarse aggregate, 12 parts of water reducer, 7 parts of SAP particles used in invention CN113416090A, 200 parts of water,

[0077] Wherein, the preparation process of the moisturizing SAP particles is:

[0078] a. Mix ammonium persulfate and water in a mass ratio of 1.1:6 and stir evenly to obtain material A.

[0079] b. Mix sodium bisulfite and water in a mass ratio of 1:5 and stir evenly to obtain material B.

[0080] c. Add acrylic acid, N-(4-ethynylphenyl) acrylamide, methoxy polyethylene glycol acrylate, polyethylene glycol diacrylate, N,N-dimethylformamide, and water into the reaction kettle at a mass ratio of 45:10:22:18:5:300, stir evenly, and obtain the base material.

[0081] d. Heat the base material, add material A and material B dropwise, keep warm and stir at 70°C for 7h to obtain a gel solution. The mass ratio of base material, material A and material B is 100:1.1:0.9.

[0082] e. The gel solution was adjusted to pH 7.3, filtered, washed, dried, and ball-milled to 50-100 nm to obtain water-absorbing resin particles.

[0083] f. Mix the water-absorbing resin particles, polyethylene glycol and water in a mass ratio of 10:1:100 and dry them to obtain the product.

[0084] After testing, the 7d compressive strength of concrete is 27.2MPa, the 7d carbonization compressive strength is 28.1MPa, the carbonization weight gain is 0.9%, the moisture retention weight gain is 0.7%, the 28d compressive strength is 43.4MPa, the 28d carbonization compressive strength is 45.0MPa, the carbonization weight gain is 1.0%, and the moisture retention weight gain is 0.1%.

[0085] Comparative Example 3

[0086] Recycled aggregate concrete is composed of the following raw materials in parts by weight:

[0087] 300 parts of cement, 130 parts of fly ash, 100 parts of mineral powder, 850 parts of recycled fine aggregate, 1010 parts of recycled coarse aggregate, 12 parts of water reducer, 7 parts of synthetic SAP particles, 200 parts of water,

[0088] Wherein, the preparation process of the synthetic SAP particles is:

[0089] a. Mix ammonium persulfate and water in a mass ratio of 1.1:6 and stir evenly to obtain material A.

[0090] b. Mix sodium bisulfite and water in a mass ratio of 1:5 and stir evenly to obtain material B.

[0091] c. Add acrylic acid, acrylamide, polyethylene glycol diacrylate, N,N-dimethylformamide and water into the reaction kettle in a mass ratio of 45:20:30:5:300 and stir evenly to obtain the base material.

[0092] d. Heat the base material, add material A and material B dropwise, keep warm and stir at 70°C for 7h to obtain a gel solution. The mass ratio of base material, material A and material B is 100:1.1:0.9.

[0093] e. The gel solution was adjusted to pH 7.3, filtered, washed, dried, and ball-milled to 50-100 nm to obtain water-absorbing resin particles.

[0094] f. Mix the water-absorbing resin particles, polyethylene glycol and water in a mass ratio of 10:1:100 and dry them to obtain the product.

[0095] After testing, the 7d compressive strength of concrete is 27.5MPa, the 7d carbonization compressive strength is 31.2MPa, the carbonization weight gain is 2.1%, the moisture retention weight gain is 3.6%, the 28d compressive strength is 44.0MPa, the 28d carbonization compressive strength is 47.1MPa, the carbonization weight gain is 4.5%, and the moisture retention weight gain is 1.2%.

[0096] Comparative Example 4

[0097] Recycled aggregate concrete is composed of the following raw materials in parts by weight:

[0098] 300 parts of cement, 130 parts of fly ash, 100 parts of mineral powder, 850 parts of recycled fine aggregate, 1010 parts of recycled coarse aggregate, 12 parts of water reducer, 7 parts of synthetic SAP particles, 200 parts of water,

[0099] Wherein, the preparation process of the synthetic SAP particles is:

[0100] a. Mix ammonium persulfate and water in a mass ratio of 1.1:6 and stir evenly to obtain material A.

[0101] b. Mix sodium bisulfite and water in a mass ratio of 1:5 and stir evenly to obtain material B.

[0102] c. Add acrylic acid, N-(4-ethynylphenyl) acrylamide, N,N-dimethylformamide and water in a mass ratio of 65:28:7:300 into the reaction kettle and stir evenly to obtain the base material.

[0103] d. Heat the base material, add material A and material B dropwise, keep warm and stir at 70°C for 7h to obtain a gel solution. The mass ratio of base material, material A and material B is 100:1.1:0.9.

[0104] e. The gel solution was adjusted to pH 7.3, filtered, washed, dried, and ball-milled to 50-100 nm to obtain water-absorbing resin particles.

[0105] f. Mix the water-absorbing resin particles, polyethylene glycol and water in a mass ratio of 10:1:100 and dry them to obtain the product.

[0106] After testing, the 7d compressive strength of concrete is 24.3MPa, the 7d carbonization compressive strength is 28.9MPa, the carbonization weight gain is 1.9%, the moisture retention weight gain is 3.1%, the 28d compressive strength is 41.1MPa, the 28d carbonization compressive strength is 45.5MPa, the carbonization weight gain is 4.3%, and the moisture retention weight gain is 0.9%.

[0107] Comparative Example 5

[0108] Recycled aggregate concrete is composed of the following raw materials in parts by weight:

[0109] 300 parts of cement, 130 parts of fly ash, 100 parts of mineral powder, 850 parts of recycled fine aggregate, 1010 parts of recycled coarse aggregate, 12 parts of water reducer, 7 parts of moisturizing SAP particles, 200 parts of water,

[0110] Wherein, the preparation process of the moisturizing SAP particles is:

[0111] a. Mix ammonium persulfate and water in a mass ratio of 1.1:6 and stir evenly to obtain material A.

[0112] b. Mix sodium bisulfite and water in a mass ratio of 1:5 and stir evenly to obtain material B.

[0113] c. Add acrylic acid, N-(4-ethynylphenyl) acrylamide, methoxy polyethylene glycol acrylate, polyethylene glycol diacrylate, N,N-dimethylformamide, and water into the reaction kettle at a mass ratio of 45:10:22:18:5:300, stir evenly, and obtain the base material.

[0114] d. Heat the base material, add material A and material B dropwise, keep warm and stir at 70°C for 7h to obtain a gel solution. The mass ratio of base material, material A and material B is 100:1.1:0.9.

[0115] e. The pH value of the gel solution is adjusted to 7.3, filtered, washed, dried, and ball-milled to 50-100 nm to obtain water-absorbing resin particles.

[0116] After testing, the 7d compressive strength of concrete is 25.7MPa, the 7d carbonization compressive strength is 30.3MPa, the carbonization weight gain is 2.2%, the moisture retention weight gain is 3.4%, the 28d compressive strength is 43.5MPa, the 28d carbonization compressive strength is 45.6MPa, the carbonization weight gain is 4.1%, the moisture retention weight gain is 0.8%.

[0117] It can be seen from Comparative Examples 1-2 that the addition of ordinary SAP below 2% of the mass of the cementitious material does not significantly improve the carbonization effect. The addition of ordinary SAP above 2% of the mass of the cementitious material and increasing the water-cement ratio can improve the relative carbonization effect, but will greatly affect the mechanical properties of the concrete. It can be seen from Comparative Examples 3-5 that the change of the monomer and whether the polyethylene glycol is loaded or not will affect the carbonization effect. The moisturizing SAP particles prepared by the present invention still have good water retention capacity as the curing proceeds, and the carbonization effect and mechanical properties of the concrete are greatly enhanced. The water release of ordinary SAP particles is relatively fast, which mainly solves the water replenishment problem in the early stage of cement hydration and prevents early drying shrinkage and plastic cracking of concrete. The internal curing effect mainly occurs in the first 3 days of cement hydration, and the water retention after 7 days decreases seriously.

[0118] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A high-efficiency carbonized recycled aggregate concrete, characterized in that: It is composed of the following raw materials in parts by weight: 280-310 parts of cement, 200-230 parts of admixture, 800-860 parts of recycled fine aggregate, 1000-1040 parts of recycled coarse aggregate, 10-12 parts of water reducer, 6-8 parts of moisturizing SAP particles, 190-210 parts of water, The preparation process of the moisturizing SAP particles is as follows: a. Mix persulfate and water in a mass ratio of (1.1-1.2):6 and stir evenly to obtain material A. b. Mix sodium bisulfite and water in a mass ratio of (0.9-1):5 and stir evenly to obtain material B. c. Add acrylic acid, N-(4-ethynylphenyl) acrylamide, methoxy polyethylene glycol acrylate, polyethylene glycol diacrylate, N,N-dimethylformamide, and water in a mass ratio of (40-50):(10-12):(20-25):(15-18):(4-6):(280-300) into a reaction kettle and stir evenly to obtain a base material. d. Heat the base material, add material A and material B dropwise, keep warm and stir to obtain a gel solution. The mass ratio of base material, material A and material B is 100:(1-1.1):(0.8-0.9). e. Adjust the pH value of the gel solution to 7.2-7.4, filter, wash, dry, and ball-mill to 50-100 nm to obtain water-absorbing resin particles. f. Mix the water-absorbing resin particles, polyethylene glycol and water in a mass ratio of 10:(1-1.2):100 and dry to obtain.

2. The high-efficiency carbonized recycled aggregate concrete according to claim 1, characterized in that: The cement is at least one of silicate cement, ordinary silicate cement, sulphoaluminate cement and aluminate cement.

3. The high-efficiency carbonized recycled aggregate concrete according to claim 1, characterized in that: The admixture is at least one of fly ash, mineral powder, silica fume, metakaolin, and activated coal gangue powder.

4. The high-efficiency carbonized recycled aggregate concrete according to claim 1, characterized in that: The particle size of the recycled fine aggregate is 0.1-4.25 mm, and the fineness modulus is 2.2-2.

4.

5. The high-efficiency carbonized recycled aggregate concrete according to claim 1, characterized in that: The recycled coarse aggregate is continuously assembled with a particle size of 5-16 mm.

6. The high-efficiency carbonized recycled aggregate concrete according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid water reducing agent, and the water reducing rate is ≥20%.

7. The high-efficiency carbonized recycled aggregate concrete according to claim 1, characterized in that: In step a, the persulfate is ammonium persulfate.

8. The high-efficiency carbonized recycled aggregate concrete according to claim 1, characterized in that: The step d is to stir and insulate at 70-75° C. for 6-8 hours.

9. The high-efficiency carbonized recycled aggregate concrete according to claim 1, characterized in that: In step e, anhydrous ethanol is used for washing.

10. The method for preparing the high-efficiency carbonized recycled aggregate concrete according to any one of claims 1 to 9, characterized in that: The steps include: 1) Weigh each raw material by weight, 2) Add cement, admixture, recycled fine aggregate and moisturizing SAP particles into a mixer and mix them evenly to obtain a dry mix. 3) Dissolve the water reducer in water to obtain an admixture solution. 4) Add recycled coarse aggregate to the dry mix, stir, add admixture solution, stir evenly to obtain concrete slurry. 5) The concrete slurry is molded, demoulded and cured.

Citation Information

Cited By

  • Reinforced recycled aggregate concrete and preparation method thereof

    CN121426513A